Coastal communities' adaptive capacity to climate change: Pantanos de Centla Biosphere Reserve, Mexico. (1st April 2022) - Ferro Azcona, Hakna; Mesa-Jurado, M. Azahara; Espinoza-Tenorio, Alejandro; Díaz Perera, Miguel Ángel; Mendoza-Carranza, Manuel; Olivera-Villarroel, Marcelo; Gómez-Pais, Gloria de las Mercedes
Abstract: Measuring the adaptive capacity of human communities living in protected natural areas subject to conservation represents a critical factor in promoting socio-ecological systems sustainability in response to the effects of climate change. This study evaluated the socioeconomic context of communities at two levels (household and community), in areas located inside and outside the Pantanos de Centla Biosphere Reserve (PCBR), Tabasco. For this, a revision of the conservation and training programs was carried out, 209 household surveys were applied, and 15 key stakeholders were interviewed. The adaptive capacity index (ACI), made up of 7 determinants and 40 indicators, shows significant differences in the adaptive capacity (AC) of localities analyzed inside and outside the PCBR. These differences can be attributed to social factors, information, and competence at the community, institutional, and human determinants. The results of this research suggest that decision-makers should encourage policies that promote AC in the studied localities to strengthen the determinants with low values in the institutional, human, and economic aspects. Highlights: Adaptive capacity measurement research in response to the effects of climate change effects is still insufficient. We developed an Adaptive Capacity Index (ACI) at the household and locality level in a protected wetland (RAMSAR site). The ACI defines significant determinants to strengthen the adaptive capacity, such as social capital and infrastructure. The ACI determined the responses to extreme hydro-meteorological events within and outside the protected area. This framework provides a line of action towards improving the future management in protected areas.